Accumulation, Development, and Exploitation in Different Colonial and Post-Colonial Contexts: Taiwan, Indonesia and the Democratic Republic of the Congo, 1900-80 - Anne Booth (Economics and Finance in Indonesia, 2015)
The Belgian Congo (Zaire, now the Democratic Republic of the Congo), the Netherlands Indies (Indonesia), and Taiwan/Formosa (now the Republic of China) experienced policies during the 19th and early 20th century which could be termed exploitative or extractive, although some policies in these colonies could also be termed developmental. All three colonies had a troubled passage to independence, and the immediate post-independence era was marked by considerable political and economic turmoil. But the growth performance of the three former colonies has been very different. Taiwan has seen very rapid growth sustained over decades; Indonesia’s economic growth since 1970 has been quite robust; the Congo has seen a growth collapse which is extraordinary even by African standards. The paper suggests some explanations for this divergence in terms of policies pursued by the Japanese, Dutch and Belgian colonial regimes, and by postindependence governments in these countries.